Development and implementation of new reference panels for HLA imputation from different populations to accelerate immunogenetic association studies - Silva, Nayane dos Santos Brito [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The Human Leukocyte Antigen (HLA) genes within the Major Histocompatibility Complex (MHC) region encode essential molecules for immune system activation. These molecules are involved in the antigen presentation pathway, presenting both self and non-self antigens. HLA gene polymorphisms are associated with many diseases and influence transplant outcomes. The analysis of HLA genes from second-generation sequencing data (also known as NGS) requires specialized tools to avoid alignment and genotyping errors. In this study, we applied the hla-mapper pipeline to call SNPs and haplotypes within HLA genes in different worldwide populations, including over 1,000 samples from Brazil. This methodology effectively analyzed HLA genetic diversity at multiple levels, encompassing SNPs, InDels, haplotypes, and alleles with 2- to 4-field resolution, as we demonstrated for the HLA-B gene (the most polymorphic HLA gene). After, within the SNP-HLA Reference Consortium (SHLARC) framework, we used the data obtained in the previous step to create and test HLA imputation models. These models were validated using an independent Brazilian sample and cross-validated within the reference panel by performing repetitive subsampling. The best results for imputation were obtained using the full reference panel, i.e., when we pooled together all samples (including Brazilians) in a single reference panel, highlighting the importance of including admixed samples in multiethnic panels. Moreover, our imputation accuracy outperformed those obtained with the Michigan Imputation Server, a widely used imputation platform for HLA genes, validating the effectiveness of our method. The findings of this work represent a significant contribution to understanding the genetic diversity of HLA genes and improving imputation techniques.

Os genes HLA (Human Leukocyte Antigen) na região do Complexo Principal de Histocompatibilidade (MHC) codificam moléculas essenciais para a ativação do sistema imunológico. Essas moléculas estão envolvidas na via de apresentação de antígenos, apresentando tanto antígenos próprios quanto não próprios aos linfócitos T. Os polimorfismos dos genes HLA estão associados a diversas doenças e influenciam os resultados de transplantes. A análise dos genes HLA a partir de dados de sequenciamento de segunda geração (também conhecido como NGS) requer ferramentas especializadas para evitar erros de alinhamento e genotipagem. Neste estudo, aplicamos o programa hla-mapper para identificar SNPs e haplótipos dentro dos genes HLA em diferentes populações mundiais, incluindo mais de 1.000 amostras do Brasil. Essa metodologia analisou de forma eficaz a diversidade genética dos genes HLA em vários níveis, abrangendo SNPs, InDels, haplótipos e alelos com resolução de 2 a 4 campos, como demonstramos para o gene HLA-B (o gene HLA mais polimórfico). Posteriormente, no âmbito do SNP-HLA Reference Consortium (SHLARC), utilizamos os dados obtidos na etapa anterior para criar e testar modelos de imputação de HLA. Esses modelos foram validados usando uma amostra brasileira independente e validados de forma cruzada dentro do painel de referência, por meio de subamostragens repetidas. Os melhores resultados de imputação foram obtidos utilizando o painel de referência completo, ou seja, quando agrupamos todas as amostras (incluindo as brasileiras) em um único painel de referência, destacando a importância de incluir amostras miscigenadas em painéis multiétnicos. Além disso, nossa precisão de imputação superou os resultados obtidos com o Michigan Imputation Server, uma plataforma amplamente utilizada para imputação de genes HLA, validando a eficácia do nosso método. As descobertas deste trabalho representam uma contribuição significativa para a compreensão da diversidade genética dos genes HLA e para o aprimoramento de técnicas de imputação.
Développement et implémentation de nouveaux panels de référence pour l'imputation HLA à partir de populations diversifiées pour accélérer les études d'association immunogénétiques
Keywords: HLA; Imputação de HLA; SHLARC; Imunogenética